ANALISIS IDIOMATIK PADA NOVEL DUA BARISTA KARYA NAJHATY SHARMA - Syafi’ Junadi; Atina Khoirun Nisa (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
Researchers limit the problems analyzed about the type of idiomatic and the meaning of the idiomatic. In this study, it is stated that there are two types of idiomaotic meanings, namely full idiom and partial idiom. This study aims to analyze idiomatic forms and types of idiomatic Indonesian. There are two types of idiomatic contained in the novel Dua Barista because Najhati Sharma in 2020, namely partial idiomatic and full idiomatic. This type of research is qualitative using data analysis methods. Therefore, the researcher took the title "The idiomatic meaning of the novel Dua Barista by Najhay Sharma". Data analysis used by using reading techniques and recording the novel Dua Barista by Najhaty Sharma. The results of this study indicate that there are full idiom types and partial idioms in the novel Dua Barista karaya Najhaty Sharma. Full idioms were found as many as eleven partial idioms and eleven full idioms, namely, nesting disease, night pekantnya, toil, khodimah, simple huts, rumors, shining like the full moon, my body is thin like the letter alif, the bridge of the nose, thousands of feet of prayer . From the data analysis, it was found that eleven full idioms and eleven partial idioms were found. So the conclusion of this study is about idiomatic analysis, which discusses idiomatic types and idiomatic meanings contained in the novel Dua Barista by Najhaty Sharma in 2020.